Morphological and Biophysical Properties of Bovine Parietal Pericardium and Tunica Vaginalis Xenografts in a Rat Model - Yagoub Mohamed, Abdel Hafeez (2005)
The study was conducted with the main objectives to evaluate the macroscopic, microscopic and biomechanical properties of lyophilized and glycerolized bovine parietal pericardium and tunica vaginalis used for repair of full thickness abdominal wall defect in the rat. Expanded polytetraflouroethylene (ePTFE) Mycro ~ e s h @was used as positive control. In addition, the effects of preservation methods used in this study on the biomechanical properties of the pre-implanted grafts were also studied. Fresh bovine parietal pericardium and tunica vaginalis sacs collected from abattoir were processed and preserved by lyophilization and glycerolization. A total of 180 adult male Sprague Dawley rats (300-400g) divided into six groups of 30 rats each were used in the study. Full thickness mid ventral abdominal wall defects of 3x2.5 cm in size were created in each rat. The defects in the first four groups of rats were repaired with the same size (3x2.5 cm) of lyophilized pericardium (IFDBP), lyophilized tunica vaginalis (IFDTV), glycerolized pericardium (GBP) and glycerolized tunica vaginalis (GTV) respectively. The remaining two groups were used as positive control and repaired with polytetraflouroethylene (ePTFE) Mycro ~esh@Th'e negative control group underwent a U shape sham-operation. Six rats fiom each group were sacrificed at post-implantation intervals of 1, 3, 6, 9 and 18 weeks for macroscopic, microscopic and biomechanical evaluations. Biomechanical evaluation of the pre-implanted grafts revealed that kze-drying has no significant effect (E-0.05) on biomechanical properties of the fresh bovine parietal pericardium and tunica vaginalis. While gamma sterilization caused significant decrease (R0.05) in biomechanical properties of the fkeeze-dried bovine pericardium and hmica vaginalis. Glycerol preservation caused significant (P<0.05) decrease in the biomechanical properties of fresh bovine parietal pericardimn, while it has no significant effect on the biomechanical properties of fiesh bovine parietal tunica vaginalis. Macroscopically, 97.66% of the rats survived until their predetermined sacrifice date. Adhesions, infections and seroma were encountered in 7.22%, 2.77% and 1.67% respectively of the rats operated. No serious post-surgical complications such as hernia, fistula and intestinal obstruction were encountered in the study. Glycerolized and lyophilized grafts were gradually resorbed and replaced by recipient tissue, while the ePTFE implants apparently remained without marked structural changes. Glycerol preservation seemed to delay the grafts resorption while lyophilization seemed to enhance grafts resorption Microscopically, the pre-implanted bovine parietal pericardium and tunica vaginalis were mainly fibro-collagenous in nature with few cellular and vascular elements. Freeze-drying and gamma sterilization has severe damaging effects on ultrastructural features of the grafts. In contrast, glycerol preservation seems to preserve the ultrastructural features of the grafts. Microscopically, the lyophilized and glycerolized grafts were replaced by collagenous tissue. Foreign body giant cells were detected in fibrous capsules around ePTFE Mycro Mesh implant starting from week three post-implantation onward. Calcium deposition was demonstrated in matrix of the ePTFE Mycro Mesh implant at 18 weeks postimplantation. No foreign body giant cells or calcium deposition were demonstrated in rats implanted with grafts of bovine origin or in sham-operated rats. The immuno-gold labeling showed that bovine type I collagen remained detectable in the implanted areas throughout the study period. The immunoperoxidase staining demonstrated that the intensity of the rat's type I collagen was increased with the advance of post-implantation intervals, while the intensity of rat's type I11 collagen showed slight changes with advance of post-implantation intervals. Post-implantation biomechanical evaluations revealed that the healing biomechanical properties between the implanted materials and the recipient abdominal tissues increased with advance of post-implantation intervals. However, there were no significant differences (P>0.05) among the overall mean values (n=15) of healing tensile strength, maximum load at break and Young's modulus of elasticity of all groups of implanted materials.